2021
DOI: 10.3390/jcm10245901
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, Development and Deformation of the Spine in Mild and Moderate Scoliosis: Are Changes in the Spine Primary or Secondary?

Abstract: Introduction and aim of the study: We aim to determine whether the changes in the spine in scoliogenesis of idiopathic scoliosis (IS), are primary/inherent or secondary. There is limited information on this issue in the literature. We studied the sagittal profile of the spine in IS using surface topography. Material and methods: After approval of the ethics committee of the hospital, we studied 45 children, 4 boys and 41 girls, with an average age of 12.5 years (range 7.5–16.4 years), referred to the scoliosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…According to many authors, rib hump deformity most likely results from asymmetric rib growth rather than from vertebral rotation, and ATR measurements correlate with apical axial vertebral rotation but only up to a certain point [ 19 , 20 ]. The residual rib hump exists even if significant vertebral derotation is carried out, due to the fixed deformity of the ribs and also the fact that ribs may continue to grow asymmetrically postoperatively if the patient still has growth potential, a phenomenon resulting in the relapse of the thoracic deformity [ 19 , 20 , 21 ]. In clinical papers, authors have not found any beneficial effects of DVR on rib hump reduction compared to methods that include no derotation [ 16 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to many authors, rib hump deformity most likely results from asymmetric rib growth rather than from vertebral rotation, and ATR measurements correlate with apical axial vertebral rotation but only up to a certain point [ 19 , 20 ]. The residual rib hump exists even if significant vertebral derotation is carried out, due to the fixed deformity of the ribs and also the fact that ribs may continue to grow asymmetrically postoperatively if the patient still has growth potential, a phenomenon resulting in the relapse of the thoracic deformity [ 19 , 20 , 21 ]. In clinical papers, authors have not found any beneficial effects of DVR on rib hump reduction compared to methods that include no derotation [ 16 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors' opinion is that "at initiating and mild scoliosis, the patho-biomechanics are probably dissimilar from the biomechanics when the curve is severe". Furthermore, we consider that at initiating and mild IS cases, genetics, epigenetics, and biology have the dominant/protagonistic aetiological role; however, we should not overlook the non-protagonistic role of patho-biomechanics at this stage, which become dominant later for progressive IS [50].…”
Section: Discussionmentioning
confidence: 99%
“…Grivas et al (2007 and2022) confirmed the role of the RC asymmetry as a leading parameter for the development of IS, concluding that in mild IS, the deformity of the thorax precedes the spinal deformity. They found that there is a lack of correlation between surface topography findings (hump) presented as TA to the Cobb angle in younger girls in mild and moderate IS and that this correlation appears later in older children [27,50].…”
Section: Rib Cage Deformity-rib Index-aetiological Implicationsmentioning
confidence: 99%
“…With great interest, we have read the article entitled “Morphology, Development and Deformation of the Spine in Mild and Moderate Scoliosis: Are Changes in the Spine Pri-mary or Secondary?” by Grivas et al, an incredibly interesting read [ 1 ]. This study covers the important but divided topic of sagittal spinal alignment as a causal factor in the etiology of idiopathic scoliosis, and we would like to compliment the authors on their work.…”
mentioning
confidence: 99%